The Influence of Socio-Cultural Background on Language Choice in Intercultural Communication in Indonesia - Irfan Aziz (Journal of Psycho Linguistics, 2025)
In the era of globalization, intercultural interaction is increasing, so understanding the influence of socio-cultural background on language choice is important, especially in a multicultural country like Indonesia. Language choice in intercultural communication is influenced by a variety of socio-cultural factors, which can affect the effectiveness of cross-cultural communication and understanding. This study aims to analyze the influence of socio-cultural background on language preferences in various contexts of intercultural communication in Indonesia. This study uses a qualitative approach, with data collection through semi-structured interviews and participatory observations. Participants were selected based on purposive sampling techniques to cover diverse socio-cultural backgrounds, including education, ethnicity, and exposure to foreign cultures. Data analysis was carried out thematically to identify relevant language preference patterns. The results of the study show that education, cultural values, and exposure to foreign cultures have a significant effect on language choice. In the family environment, regional languages are more dominant, while Indonesian and English are often chosen in professional and intercultural contexts. In conclusion, socio-cultural background shapes individual language preferences, which can strengthen cultural identity and improve the effectiveness of intercultural communication. The practical implications of this research are to provide guidance for communication practitioners and policymakers to design communication strategies that are inclusive and respectful of cultural diversity.